Microalgae for biotechnological applications: Cultivation, harvesting and biomass processing - Morais Júnior, Wilson Galvão (2020)
In either unicellular or multi-cellular form, microalgae are photosynthetic microorganisms, mainly known for being part of the human diet in several world regions. More recently, they have been in the spotlight of researchers, not only because of their nutritional value, but also due to their high value-added components. This work reviews five microalgae genera: Dunaliella, Botryococcus, Chlamydomonas, Chlorella and Arthrospira, considered among the most promising for commercial biotechnological applications. The analysis shows that, although the research paradigms are generally shared among species, parameterization changes of culture environment and stress conditions, several applications can be envisaged for the cultivated species, which is discussed in this work. Besides, several applications in which these microalgae are being widely used, or are intended to be used, are analyzed and discussed. The potential applications depend on the type of metabolites found in each microalgae species, which is discussed in this work, giving examples of application and describing methods for their cultivation, harvesting and biomass processing. Thus, in addition to being used in human diet supplementation, microalgae can be used as ingredients for animal feed, medicines, cosmetics pigments, biofuels, bioplastics and biostimulants.